KONDISI PENCEMARAN LINGKUNGAN PERAIRAN DI TELUK JAKARTA - Sachoemar, Suhendar I.; Wahjono, Heru Dwi (Jurnal Air Indonesia, 2007)
The environment of the rivers surround Jakarta was polluted due to the increasing of the domestics and industrial waste as response to the rapid development of the anthropogenic activities within the city since the decades. As consequence, the carrying capacity of the water ecosystem was degraded including Jakarta Bay as the estuary of the passing rivers of the Jakarta City. This article briefly discusses the pollution problem within the Jakarta Bay that is supported by the data collected from various sources including the result from in-situ survey. The result has shown the fact of what the causing factors that stimulated the pollution problem within this area. Ã‚Â Katakunci : Pencemaran Lingkungan Perairan. Teluk Jakarta, Pantai Utara Jakarta, Air Limbah Domestik, Beban Pencemaran.